Apakah Manajemen Laba dan Tipe Struktur Kepemilikan Institusional dapat Meningkatkan Nilai Perusahaan? - Prabowo, Ananto (Jurnal Akuntansi Keuangan dan Bisnis, 2022)
The purpose of this research is to empirically identify the influence of earnings management and corporate governance toward firm value. Good corporate governance is measured by two types of institutional ownership: long-term/pressure-resistance and short-term/pressure-sensitive. The purposive sampling method is being utilized to do sampling on property, real estate & building construction firms which are listed at the Indonesian Stock Exchange (IDX) for the period of five years (2016-2020). In accordance with the method is identified 53 firms that are suitable for the research with a total sample of 265 firm-years observasion. Weighted least square regression method is implemented to test hypothesizes. The result indicates that earnings management positivelyffect the firm value. In addition, market risk and sales growth able to increase firm value measured by Tobin’s Q ratio.